Legal Consequences of Transferring the Name of Land Certificate on Unpaid Sales - Irfan Anas; Yudha Cahya Kumala; Supaphorn Akkapin (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2025)
This research examines the legal consequences of the transfer of the name of the land certificate in an unpaid sale and purchase transaction. The purpose of this study is to analyze how the process of transferring land rights can occur even though payment has not been fully implemented, as well as to identify the legal implications arising from incomplete payment in land sale and purchase transactions. Through a normative legal analysis approach, this study concludes that the transfer of land rights that have not been paid in full can lead to legal uncertainty, both in relation to the validity of the transaction and the potential for future property rights disputes. Therefore, stricter regulations and better supervision of land transactions that have not met the full payment requirements are needed. This research is expected to contribute to the development of agrarian law and become the basis for more effective policy recommendations in order to provide legal certainty in the transfer of land rights.